Emerging Trends of Artificial Intelligence in Education (2021–2026): A Bibliometric Analysis of Curriculum and Vocational Education Transformation - Amy Theresia Sipayung; Rusman; Ahmad Fajar Fadlillah (Universitas Muhammadiyah Sumatera Utara, 2026)
Artificial intelligence (AI) increasingly reshaped educational practices, prompting growing scholarly inquiry into its pedagogical, curricular, and environmental implications. However, existing bibliometric reviews of Artificial Intelligence in Education (AIED) predominantly predated the generative AI inflection point and rarely disaggregated vocational education as a distinct theme. This study examined the intellectual structure and thematic evolution of AIED research published between 2021 and 2026, focusing on how curriculum development and vocational education transformation were represented within the field. Bibliographic data were retrieved from Scopus using the query